Pathology-associated change in levels and localization of SIDT2 in postmortem brains of Parkinson's disease and dementia with Lewy bodies patients. (January 2022) - Fujiwara, Yuuki; Kabuta, Chihana; Sano, Terunori; Murayama, Shigeo; Saito, Yuko; Kabuta, Tomohiro
Abstract: Parkinson's disease (PD) and dementia with Lewy bodies (DLB) are major neurodegenerative disorders that share commonalities in their pathology involving the formation of Lewy bodies, the main component of which is α-synuclein protein. Aberrancy and dysfunction in lysosomes have been suggested to play critical roles in the pathogenesis of Lewy body diseases. We recently identified a novel lysosomal degradation pathway in which various macromolecules, including α-synuclein protein, are directly imported into lysosomes and degraded. In this study, we analyzed the levels and localization of the lysosomal membrane protein SIDT2, a key factor in this pathway, in the postmortem brains of patients with PD and DLB. The levels of SIDT2 protein were significantly higher in the anterior cingulate cortex (ACC) of both PD and DLB cases than in age-matched control subjects, but this difference was not observed in the inferior frontal gyrus. The levels of SIDT2 also showed a strong correlation with α-synuclein levels in the ACC of all subjects, including controls. SIDT2 was colocalized with aggregates positive for phosphorylated α-synuclein protein, which is a hallmark of Lewy bodies, in all examined cases of both PD and DLB. These observations suggest that changes in the levels and localization of SIDT2 occur at the lesion site of Lewy body diseases in accordance with the progression of Lewy body pathology. Our findings provide mechanistic insights into the pathogenesis of Lewy body diseases, as well as other neurodegenerative disorders, and may provide clues for improved diagnosis, prevention, and therapeutic intervention for such diseases. Highlights: SIDT2 was increased in the ACC of patients with Lewy body disease. The increase of SIDT2 was not observed in the IFG of the same patients. SIDT2 and α-synuclein levels showed a strong correlation in the ACC of all subjects. SIDT2 and phosphorylated α-synuclein colocalized in the ACC of patients. α-synuclein protein was increased in aged Sidt2 deficient mice brains; mRNA was not.